Policy issues in West African integration - Peter Robson (Intereconomics, 1983)
As a result of the slight success achieved by many developing countries in their attempts to become integrated in the international division of labour and the growing fear of unilateral dependence upon the industrial nations, increased attention has been given in recent years to economic and technical cooperation between developing countries. Peter Robson examines the potential and limitations of regional integration between developing countries in the light of the experience of West Africa. This is followed by an article by Norbert Wagner who discusses the regional integration issue using South and South-East Asia as examples.
Keywords: 330; Regional Integration